The effect of precipitation hardening on the structure and mechanical and tribological properties of magnesium alloy WE54. (May 2017) - Barylski, A.; Kupka, M.; Aniołek, K.; Rak, J.
Abstract: The paper examined changes in the properties of magnesium alloy WE54 which occur as a result of precipitation hardening. Solution treatment was performed for 8 h at a temperature of 545 °C, followed by cooling in ice water (0 °C), and in hot water (95 °C). After the solution treatment, the examined alloy was aged at 250 °C for 8–48 h. The as-received alloy was characterised by a fine-grained structure comprised of solid solution α-Mg as well as Mg41 Nd5 and Mg24 Y5 precipitates. Zirconium-rich areas were also observed. The ageing of alloy caused the formation of phase β, which consisted of compound Mg12 NdY. It has been found that both the temperature of the coolant used during the solution treatment and the duration of ageing significantly affected mechanical properties. Tribological tests showed a more than fourfold reduction in the volumetric wear and a more than threefold reduction in the linear wear after ageing. Highlights: The solution treatment caused intensive growth of the average size of the grains. The volume fraction of precipitates increased threefold with increased ageing time. An increase in hardness and Young's modulus was observed after ageing. Changes in mechanical properties and structure caused a significant decrease in the wear and the friction coefficient.